Electrochemically and Photochemically Induced Hydrogen Evolution Catalysis with Cobalt Tetraazamacrocycles Occurs Through Different Pathways. Issue 10 (6th April 2020) - Grau, Sergi; Schilling, Mauro; Moonshiram, Dooshaye; Benet‐Buchholz, Jordi; Luber, Sandra; Llobet, Antoni; Gimbert‐Suriñach, Carolina
Abstract: Cobalt complexes containing equatorial tetraazamacrocyclic ligands are active catalysts for the hydrogen evolution reaction in pure aqueous conditions. We investigated the effect of different groups directly linked to the macrocyclic ligand (−NH−, −NCH3 −, or −N(CH2 OH)−). In electrochemically induced hydrogen evolution catalysis at pH 4, the rate determining step is the protonation of the reduced Co I species that gives a cobalt hydride (Co III −H), a key intermediate towards the H−H bond formation. In sharp contrast, under photochemical conditions using [Ru(bpy)3 ] 2+ (bpy=2, 2'‐bipyridine) as a photosensitizer and ascorbate as sacrificial electron donor, the formation of a Co 0 species that quickly protonates to give a Co II −H is proposed. In this scenario, the rate determining step is the H−H bond formation that occurs in an intermolecular fashion from the Co II −H species and a water molecule. Both mechanisms are supported by DFT calculations, which allowed us to estimate the pKa values of the Co III −H and Co II −H species and transition states based on intramolecular and intermolecular H−H bond formation from Co II −H. Abstract : Two different ! The relative rates and mechanistic pathways of hydrogen evolution catalysis by cobalt complexes bearing a tetraazamacrocyclic ligand are dependent on the catalytic conditions. Under electrochemical driven catalysis, the rate determining step (RDS) is the protonation of the Co I intermediate, whereas intermolecular H−H formation is the RDS for photochemically induced reactions using [Ru(bpy)3 ] 2+ (bpy=2, 2'‐bipyridine) as photosensitizer.